A Study to Assess the Drug Consumption and Rationality in the Prescription of Outpatients Undergoing Periodontal Treatment: Pharmaceutical Science-Pharmacology - Chaudhary, Amit; Sharma, Dharmesh; Negi, Rajan; Supehia, Sakshi; Thakur, Malvika (International Journal of Life Science and Pharma Research, 2022)
Drug utilisation research is essential in clinical practice because it serves as the foundation for implementing changes to drug dispensing rules at the local and national levels. The ultimate goal of such a study is to make drug usage more reasonable. This prospective cross-sectional study aimed to collect data on drug utilisation among dental patients from Himachal Pradesh’s Department of Periodontics to identify possible targets for improving drug prescribing habits. After applying inclusion and exclusion criteria, data were collected prospectively from a total of 849 medical records of patients. The patient’s information included their OPD number, age, sex, health problem description, and prescription parameters, including medicine name, route, strength, dose form, quantity, duration, investigations, provisional diagnosis, and therapy. Prescriptions were analysed using WHO core drug indicators and WHO ATC/DDD approach to calculate drug consumption. The most prescribed antibiotic was amoxicillin, separately or in combination. The number of DDD consumed and the DDD/1000 population/day was the maximum for vitamins, followed by antibacterial and non-steroidal anti-inflammatory drugs. The average number of drugs per encounter was 2.2. The percentage of encounters with an antibiotic in prescription was very high i.e., 72.3%. Only 37.6% of medications were prescribed, from NLEM 2015, and 14.60% generic names were prescribed. The dental practitioners did not adhere to WHO prescribing guidelines. The lowered number of prescriptions for generic names was a subject of worry